Are social inequalities in early childhood smoking initiation explained by exposure to adult smoking? Findings from the UK Millennium Cohort Study. - David C Taylor-Robinson; Sophie Wickham; Melisa Campbell; Jude Robinson; Anna Pearce; Ben Barr (PLoS ONE)
Introduction To assess the socio-economic gradient in early smoking initiation at age 11 years and the extent to which any inequality was explained after accounting for longitudinal exposure to adult smoking. Methods Analysis of the UK Millennium Cohort Study, based on 9, 609 children from ages 9 months to 11 years. The outcome was smoking initiation by age 11. Odds ratios (ORs) for smoking initiation were estimated using logistic regression, according to maternal education, whilst adjusting for baseline demographic factors. Longitudinal exposure to a regular smoker in the same room was assessed as potential mediator of the association between maternal education and early smoking, along with other socially patterned risk factors for early smoking initiation, such as parental separation and mental health. Results Overall 2.7% (95% CI: 2.3-3.1) of children had tried a cigarette by age eleven. Children of mothers with no qualifications were more than six times as likely to have tried a cigarette than children of mothers with degree level qualifications or higher (OR 6.0 [95%CI 3.5-10.1]), with clear social gradient. Controlling for potentially mediating variables, particularly exposure to a regular adult smoker reduced the OR smoking initiation in children of mothers with no qualifications by 63% (aOR 2.9 [95%CI 1.7 to 5.1]). Conclusions Smoking initiation is more common in disadvantaged children, and this is largely explained by regular exposure to an adult smoker in the same room. Reducing adult smoking in front of children may reduce inequalities in smoking initiation in children by over a half.